Smart Contracts: Assessing the Validity and Enforceability of Civil Law in Blockchain-Based Transactions - Sukardi, Didi (Raudhah Publisher, 2024)
Smart contracts are an innovation that emerged along with the development of blockchain technology, offering automation in the implementation of agreements without third-party intervention. However, the existence and application of smart contracts in the context of civil law still raises various questions regarding their validity and enforcement. This study aims to explore the legal challenges faced by smart contracts, as well as how civil law can accommodate and enforce agreements made in digital form. The research methodology used is qualitative analysis through literature studies and interviews with legal experts and industry practitioners. The results of the study show that although smart contracts offer efficiency and transparency, there are concerns regarding validity, legal recognition, and potential disputes. The novelty of this study lies in the integration of positive law and technology perspectives in understanding the dynamics between smart contracts and civil law. The social implications of this study include the need to develop adaptive regulations to regulate smart contracts, as well as increasing public understanding of the risks and benefits of using technology in legal transactions.